The influence of ph and waterborne metals on egg fertilization of the blue mussel (Mytilus edulis), the oyster (Crassostrea gigas) and the sea urchin (Paracentrotus lividus) - Riba, Inmaculada; Gabrielyan, Bardukh; Khosrovyan, Alla; Luque, Angel; Del Valls, T. Angel (Environmental Science and Pollution Research, 2016)
This study evaluated the combined effect of pH and metals on the egg fertilization process of two estuarine species, the blue mussel (Mytilus edulis), the oyster (Crassostrea gigas) and a marine species, the sea urchin (Paracentrotus lividus). The success of egg fertilization was examined after exposure of gametes to sediment extracts of various degrees of contamination at pH 6.0, 6.5, 7.0, 7.5 and 8.0. At the pH levels from 6.5 to 8.0, the egg fertilization of the different species demonstrated different sensitivity to metal and/or acidic exposure. In all species, the results revealed that egg fertilization was almost completely inhibited at pH 6.0. The egg fertilization of the blue mussel M. edulis was the least sensitive to the exposure while that of the sea urchin P. lividus demonstrated a concentration-dependent response to the pH levels from 6.5 to 8.0. The results of this study revealed that acidity increased the concentration of several metal ions (Cr, Ni, Cu, Zn, Cd, and Pb) but reduced its availability to the organisms, probably related to the reactivity of the ions with most non-metals or to the competition among metals and other waterborne constituents.